PENGARUH GENDER DAN LATAR BELAKANG PENDIDIKAN CEO TERHADAP KINERJA KEUANGANNPERUSAHAAN GO PUBLIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - AMANAH JANNAH TULLAH, NUR (Jurnal Akuntansi AKUNESA, 2017)
This study testing the influence of gender and education background of Chief Excecutive Officier (CEO) can affect the financial performance of the company. This research method is quantitative. The data used innthis study is secondary datanof company data listed in Indonesia Stock Exchange (IDX). Samples are selected by using pusposive sampling method. The samples used in this study are 154 companies (if multiplied by the number of years which was 5 years, we found 770 sample companies). The techniquenused in this research isnnon-parametric data testing due to the non-normal distribution data, by testing two independent sample tests. The resultsnof this study indicatenthe gender (male and female) and educational background (undergraduate/graduate) can affect the financial performance of the company.